2004
DOI: 10.1167/iovs.03-0667
|View full text |Cite
|
Sign up to set email alerts
|

Age, Blood Pressure, and Vessel Diameter as Factors Influencing the Arterial Retinal Flicker Response

Abstract: A significant correlation of age and bFR was not found in the small sample examined. Untreated arterial hypertension appeared to be associated with a reduced flicker response. The value of such functional vessel properties in the screening of vasosclerosis and in diagnostics in arterial hypertension should be examined in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
3
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 21 publications
14
131
3
6
Order By: Relevance
“…This finding is in agreement with several previous reports indicating impairment of blood flow regulation in the retina before the clinical appearance of retinopathy (21,29). In our study we showed an association between flicker response and age; however, the coefficient of correlation was weak, which is in agreement with previous reports (30). For example, Jeppesen et al (31) reported significantly reduced diameter response in normal individuals aged Ͼ40 years.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with several previous reports indicating impairment of blood flow regulation in the retina before the clinical appearance of retinopathy (21,29). In our study we showed an association between flicker response and age; however, the coefficient of correlation was weak, which is in agreement with previous reports (30). For example, Jeppesen et al (31) reported significantly reduced diameter response in normal individuals aged Ͼ40 years.…”
Section: Discussionsupporting
confidence: 93%
“…Recent small sample size studies demonstrated a reduced flicker response in retinal arteriole dilation in hypertension. 94,95 These studies suggest that the flicker response of retinal vessel diameter could be a new and noninvasive method for detecting early functional damage (endothelial dysfunction) and may potentially indicate the improved microvascular function under antihypertensive therapy.…”
Section: Assessment Of Dynamic Retinal Vascular Changesmentioning
confidence: 99%
“…In contrast, the DVA doesn't require much training, and the measurement can be performed in less than 15 min. The DVA quantifies non-invasively retinal vessel dilation in response to flickering light, 8 which is believed to reflect endothelial function, given the documentation of the role of nitric oxide played in this flickering light induced retinal vasodilation. [9][10][11][12] The strength of this study is to extend the application of DVA beyond whites and confirm the same …”
Section: Current Eye Researchmentioning
confidence: 99%
“…Previous clinical studies using the DVA have shown the impaired dilation to this flicker, reflecting possibly endothelial dysfunction, is associated with systemic diseases, 13 including hypertension 8 and diabetes, 14 and ocular diseases, such as diabetic retinopathy 14 and glaucoma. 15 However, although DVA has previously been shown to be reproducible in whites, 16 there have been no similar data in groups/races other than whites, including Asians.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation